An optimal integrated control strategy of urban expressway and adjacent signalized intersection with rolling horizon framework in MPC method - Linghui Xu; Yuan Zheng; Shuichao Zhang; Longjian Wang; Xinke Fan (PLoS ONE, 2025)
Urban expressway congestion around on-ramp bottlenecks is associated with traffic conditions on the main road, on-ramp and adjacent signalized intersection. Existing coordinated control strategies have rarely considered these components as a unified system. To enhance traffic system operation, this paper proposes an optimal integrated control strategy based on the model predictive control (MPC) method. Within the rolling horizon control framework, this strategy integrates ramp metering and intersection signal timing. To validate its effectiveness, simulation scenarios were developed in VISSIM software, based on a section of the South Ring Road in Ningbo, China. In contrast, the proposed strategy overall outperforms the other two referring strategies, as it improves mainline and on-ramp traffic. Additionally, traffic operation of movements at the intersection is slightly better. Therefore, the integrated control strategy ensures mainline traffic efficiency while balancing on-ramp and intersection traffic. Comparatively, referring strategy 2 exhibits poorer performance at the on-ramp and intersection, which optimally coordinates mainline speed limit, ramp metering and intersection signal timing. Traffic fluctuations on the main road due to dynamic speed limits have a negative impact on overall traffic performance.